Design and Interlocking Stability of Slope Protection Block of H-Type Gravity Mutual-Aid Steel Slag Core Concrete - Hongda Lin; Xiaolong Yu; Guangzhen Zhang; Honglei Chang; Jian Liu (Advances in Civil Engineering)
At the present, the natural stone used for traditional block rock revetment is becoming increasingly scarce, and other commonly used revetment types also have some problems, such as poor stability, complex fabrication and installation process, and large investment. Therefore, it is imminent to study a new type of reinforcement of dangerous dam banks with both ecological and environmental protection functions to meet the requirement of river flood stability. Combining theoretical calculation with laboratory tests, a new slope protection block of H-type gravity mutual-aid steel slag core concrete (H-type gravity mutual-aid steel slag core concrete block hereinafter), which is composed of an ordinary concrete shell and a steel slag core, is designed as an improvement of revetment reinforcement type and for solid waste utilization and resource saving. The indoor test method shows that the optimal shell thickness of the new block is 6 cm, and the steel slag of a single block can replace the natural aggregate ratio of 25%. The new block has concave and convex structures to enhance the interlocking effect between blocks. The compressive strength of the new block is tested by the drilling core compressive strength test to meet the strength requirement of the revetment works. Moreover, on the basis of the overall stability test platform of the interlocking block and numerical simulation analysis, the H-type gravity mutual-aid steel slag core concrete block was proved to have a better interlocking effect than the traditional blocks and exhibits excellent overall stability.